Agri-waste and microbes for production of sustainable nanomaterials - Abd-Elsalam, Kamel, 1969-; Periakaruppan, Rajiv; Rajeshkumar, S. (Nanobiotechnology for plant protection., 2022)
Agri-Waste and Microbes for Production of Sustainable Nanomaterials assesses the most recent trends used to produce bionanomaterials from agricultural waste and microorganisms. The book covers the green synthesis of various nanomaterials using microorganisms and agricultural waste, including the synthesis and characterization of green nanomaterials, the production of nanomaterials from agri-waste, including metallic, copper, silica, cellulose, nanopolymers and nano/micro plastics, and biological methods such as agricultural and microbial synthesis of metallic/metal oxide, magnetic, silver, copper, nanomaterials and nanonutrients. This is an important reference source for plant scientists, materials scientists and environmental scientists who want to understand this new generation of sustainable nanomaterials. The synthesis of nanocellulose materials from agri-wastes is an emerging alternative for waste treatment methods, developing new biosensors and antimicrobial agents. Silicon nanoparticles are an additional ingredient for the improvement of crop yields. With recent advances in nanomaterials synthesis performance and the discovery of their biomedical, environmental and agricultural applications, it is hoped that the implementation of these methods will be used at large-scale for industrial applications in different sectors.